„Droga Pani Aniu” : Debiut książkowy, tajniki typografii i serdeczna przyjaźń w świetle korespondencji Anny Frajlich-Zając ze Stanisławem Gliwą .......... 385 - Wolski, Jan (Tu jestem / zamieszkuję własne życie : studia i szkice o twórczości Anny Frajlich, 2018)
„DEAR MS. ANIA”: LITERARY DEBUT, TYPOGRAPHICAL ARCANA AND DEEP FRIENDSHIP IN THE LIGHT OF THE CORRESPONDENCE OF ANNA FRAJLICH-ZAJĄC WITH STANISŁAW GLIWAThe article discusses the circumstances surrounding the publication of Anna Frajlich’s poetic debut by the publishing house Oficyna Stanisława Gliwy, using the correspondence between the poet and the typographer preserved in the Emigration Archive in Toruń. These highly specific personal documents are from the time period between 1975 and 1986. Their correspondence was teeming with details describing the printing process, ways in which small artistic “private press” publishers function, but also very interesting opinions and judgments on poetry, everyday matters, publishing plans, travels, or exhibitions. It’s also a testimony to a friendship growing stronger as the time passed.